If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 = 18 + 2x Reorder the terms: -3 + 5x = 18 + 2x Solving -3 + 5x = 18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 5x + -2x = 18 + 2x + -2x Combine like terms: 5x + -2x = 3x -3 + 3x = 18 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 3x = 18 + 0 -3 + 3x = 18 Add '3' to each side of the equation. -3 + 3 + 3x = 18 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = 18 + 3 3x = 18 + 3 Combine like terms: 18 + 3 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| -10x=-100 | | 18x^2+12x+2=0 | | x+y+z=2 | | x+y-4z=-3 | | g+12=5k | | 2w-5=11 | | 8x-17=71 | | 2(x+4)=7(x-3)+34 | | X+1=-x+7 | | 2x-3y-2z=5 | | 10p-3=p+15 | | v+(v-22)+(v+21)=491 | | X+2=-2x+20 | | 6u=222 | | z+5=-13-5z | | 9q=108 | | 20=-11z-2 | | 20=-1z-2 | | 10xn= | | X^2+9X^2+20=0 | | 90+x=3x+2 | | 7x-3(2x+7)=-12 | | 9x-8-5x= | | 14=9+f | | 3(x+5)=x+7 | | y=2x+26 | | 12a+5=6(2a+5) | | 21x-11=10 | | 3x+4y=17 | | x-1.07=-8.5 | | 4m-7m=18 | | 3(5x-4)=4(3x-2) |